Caracterização da coordenação dos membros inferiores e avaliação dos efeitos de um treino da marcha em esteira com aumento de carga em sujeitos com doença de Parkinson - Filippin, Nadiesca Taisa (Universidade Federal de São Carlos, 2009)
The influence of the Parkinson s disease (DP) on lower limbs coordination during walking is still not completely known. The intra and interlimb coordination are essential during walking and an impairment in the motor control may affect them. On the other hand, studies about the effects of walking training with additional body load in PD are lacking. There is evidence that the increase of body load during treadmill walking improves reflex activity and leg extensor muscle activity, which are impaired in subjects with PD. Furthermore, the PD affects the quality of life of the subjects. For these reasons, two studies were accomplished. The purpose of the Study I was to compare the intralimb and interlimb coordination during walking between subjects with PD and healthy control subjects. Ten subjects with PD (PG) and ten control subjects (CG) were submitted to a clinical evaluation and a gait kinematic evaluation. The PG presented larger stride duration, stance and swing phase durations and smaller stride length, speed, cadence and joint range of motion than CG. The intra and interlimb coordination do not differ significantly between groups. These results indicate that the PG presented spatial-temporal variables and joint range of motion alterations but it was able to adapt to the limitations imposed by the disease and accomplish a functional gait, without undermine the intra and interlimb coordination pattern. The purpose of the Study II was to assess the effects of treadmill walking training with additional body load on the quality of life, motor functions and gait of subjects with PD. Nine subjects with idiopathic PD, in moderate stage, participed in this study. The training program was divided into three phases: treadmill training with additional body load (A1), control condition (conventional physical therapy group) (B) and treadmill training with load again (A2). Each phase lasted six weeks. Both evaluations and training were performed during on-phase of the medication cycle. The results showed an improvement in total score, and mobility, activities of daily life and cognition subscores related to quality of life and an improvement in the motor functions. Significant increase in propulsive forces, stride length, speed, and maximum hip extension during stance were also observed after the training program. In conclusion, the treadmill training with additional body load promoted an improvement in different aspects related to quality of life and in important variables for the maintenance of the functional gait of subjects with PD, and it is a promising alternative to optimize the rehabilitation process in combination with conventional physical therapy.
Keywords: Funções motoras; Parkinson, Doença de; Coordenação motora; Marcha; Esteira; Qualidade de vida; Parkinson s disease; Coordination; Treadmill; Load; Gait; Quality of life; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL